An inclusive end-user development framework for tailorable games - Garcia, Franco Eusébio (Universidade Federal de São Carlos, 2019)
Following the growing purposes and applications of digital games, the creation of this interactive media has been becoming more popular. Industry and academy alike have studied and created tools, methods, and techniques to allow end-users to develop their own games. However, intended audiences are still restricted (normally to anglophone youngsters without physical, cognitive, and emotional disabilities). To overcome barriers, it is necessary to allow people with different interaction abilities and needs to contribute on game development. This thesis presents an end-user development framework for tailorable games, with the purpose of promoting inclusive creation of inclusive games. Our lemma is games for everyone, by everyone. The thesis starts from the hypothesis that if end-users used creation tools suitable to their interaction needs and followed a collaborative work model to iteratively improve accessibility features to be inserted into a software architecture able to modify human-computer interaction at use-time, then they would be able create games satisfying heterogeneous interaction needs of possible players. In this thesis, we have explored documental research (systematic review to identify current approaches), creation and specification (for required software systems, models, and architectures), and field research (to understand interaction requirements and evaluate the framework). The framework encompasses a formal software architecture for implementing inclusive games, a collaborative work model for co-creation of inclusion, and an end-user game development platform (Lepi). Our framework was used by an audience not yet considered by the Literature (adult people -- some of which with low literacy and that had never used a computer before -- undergoing supervision for alcohol and drug abuse rehabilitation) over four months. Our results show that the participants were able to create games that satisfied their own interaction needs, as well as those from people with different needs than theirs (therefore, they have confirmed our research hypothesis). We have also observed that game creation and play transformed the participants. The benefits went beyond software co-creation, towards self-improvements. In this way, we have contributed with participatory and universal to creation and access of knowledge by the Brazilian citizen. Moreover, as the architecture allows continuous inclusion of new audiences via the addition of new alternatives of use, we hope that we can continue enabling more people to create and play -- small steps from users, giant leaps towards universal access.
Um framework para o desenvolvimento inclusivo de jogos digitais ajustáveis por usuários finais
Keywords: Acessibilidade em jogos; Acesso universal; Design participativo; Design universal; Design de jogos; Interação humano-computador; Jogos; Sistemas colaborativos; Accessibility; Collaborative systems; Game accessibility; Game design; Games; Human-computer interaction; Participatory design; Universal access; Universal design; End-user development; Human-centered computing; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO